Congenital diaphragmatic hernia with fetal hydrops causing postoperative intestinal perforation: An unusual manifestation seen in a neonate - Noboru Oyachi; Fuminori Numano; Tamami Fukatsu; Atsushi Nemoto; Atsushi Naito (Journal of Pediatric Surgery Case Reports, 2022)
Congenital diaphragmatic hernia (CDH) is a common cause of neonatal mortality. If CDH is associated with non-immune fetal hydrops (FH), the mortality rate is even higher. However, the pathogenesis and management of FH associated with CDH are still under discussion. We present here a case of left-sided CDH accompanied by prolonged FH, where unexpected ileal perforation developed after CDH repair.The female patient was diagnosed with left-sided CDH with right-sided pleural effusion (PE) at 26 weeks' gestation. At 35 weeks' gestation, FH progressed with bilateral PE and the patient was delivered by cesarean section with a body weight of 2068 g and Apgar 3/7. Subcutaneous edema progressed, but PE attenuated with improvement of pulmonary hypertension, and CDH repair was performed on Day 4. Postoperatively, the patient's pulmonary hypertension worsened, and intestinal perforation was observed on Day 11. In the emergency laparotomy, there was a single small bowel perforation of 5 mm in diameter in the terminal ileum. A 5 cm of the ileum was resected and the bowel was anastomosed in a single stage. The patient was weaned from the ventilator on Day 28. Although bilateral periventricular leukomalacia was confirmed, the patient was discharged without significant neurological symptoms on Day 76.